Furan and Methylfurans in Foods: An Update on Occurrence, Mitigation, and Risk Assessment. Issue 3 (12th February 2019) - Kettlitz, Beate; Scholz, Gabriele; Theurillat, Viviane; Cselovszky, Jörg; Buck, Neil R.; O' Hagan, Sue; Mavromichali, Eva; Ahrens, Katja; Kraehenbuehl, Karin; Scozzi, Gabriella; Weck, Markus; Vinci, Claudia; et al.
Abstract: The acceptance of many foods is related to traditional cooking practices, which create taste and texture and are important to digestibility, preservation, and the reduction of foodborne illnesses. A wide range of compounds are formed during the cooking of foods, a number of these have been shown to lead to adverse effects in classical toxicological models and are known as food processing contaminants (FPC). It is essential that the presence and effects of such compounds alone and in combination within the diet are understood such that proportionate risk management measures can be developed, while taking a holistic view across the whole value chain. Furan and alkylfurans (principally 2‐ and 3‐methylfuran) are highly volatile FPC, which are formed in a wide range of foods at low amounts. The focus of research to‐date has been on those foods, which have been identified to be most consequential in terms of being sources of exposure, namely jarred and canned foods for infants and young children (meals and drinks) and coffee (roast and ground, soluble). This report presents (i) new industry data on the occurrence of furan and methylfurans in selected food categories following previous coffee studies, (ii) the most salient parameters that impact furan formation, and (iii) aspects of importance for the risk assessment.